2016
DOI: 10.1016/j.clinph.2015.06.021
|View full text |Cite
|
Sign up to set email alerts
|

An improved electrical impedance myography (EIM) tongue array for use in clinical trials

Abstract: Objectives Electrical impedance myography (EIM) measurements of the tongue could provide valuable information about bulbar dysfunction in amyotrophic lateral sclerosis (ALS). A prototype tongue depressor EIM array produced gag reflexes. The objectives of this study were to determine the reliability, mean phase values, and tolerability of tongue EIM measurements using a smaller electrode array. Methods Tongue EIM measurements were performed in a total of 31 healthy individuals and four neuromuscular patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 15 publications
3
13
0
Order By: Relevance
“…EIM measurements of the tongue were performed using a commercially available bioimpedance system (Imp SFB7; Impedimed, Inc., Sydney Australia) connected to a small linear tongue array . Participants were asked to open the mouths.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…EIM measurements of the tongue were performed using a commercially available bioimpedance system (Imp SFB7; Impedimed, Inc., Sydney Australia) connected to a small linear tongue array . Participants were asked to open the mouths.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, disease‐related changes in muscle translate into EIM phase values that are lower than those recorded from healthy muscle; qualitatively, this discrepancy has been more apparent at frequencies of between approximately 50 and 500 kH z . Accordingly, quantitative phase differences between healthy and diseased muscle may also be greater at frequencies between 50 and 500 kH z .…”
Section: Measures Of Bulbar Function and Tongue Condition More Commonmentioning
confidence: 97%
“…These modeled results were then compared to previously published human data (McIlduff et al, 2015). Specifically, all human studies had been approved by Beth Israel Deaconess Medical Center’s institutional review board and informed consent had been obtained from all subjects.…”
Section: Methodsmentioning
confidence: 99%
“…Basic geometric model of tongue with electrodes on surface. B. Tongue electrode array used in the developed finite element model, using the same design as in McIlduff, et al(McIlduff, CE, Yim S, Pacheck A, Geisbush T, Mijailovic A 2015) C. Same model as in A, now with finite element mesh added.…”
Section: Figurementioning
confidence: 99%
“…This is especially important as there are few easily quantifiable assessment tools available. Recent studies have shown EIM's ability to discriminate ALSaffected tongue from healthy tongue using a simple 4electrode array constructed on a tongue depressor or similar base [80,81], using both single and multifrequency phase data. Further, a computer modeling study has shown that changes in impedance with tongue atrophy likely reflect tongue properties and are not simply an effect of decreasing tongue volume with disease progression [82].…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%